Supporting Health Among Young Men Who Have Sex With Men and Transgender Women With HIV: Lessons Learned From Implementing the weCare Intervention. Issue 5 (September 2020) - Tanner, Amanda E.; Mann-Jackson, Lilli; Song, Eunyoung Y.; Alonzo, Jorge; Schafer, Katherine R.; Ware, Samuella; Horridge, Danielle N.; Garcia, J. Manuel; Bell, Jonathan; Hall, Elias Arellano; Baker, Logan S.; Rhodes, Scott D.
Young gay, bisexual, and other men who have sex with men and transgender women with HIV, particularly those who are racial or ethnic minorities, often have poor health outcomes. They also utilize a wide array of social media. Accordingly, we developed and implemented weCare, an mHealth (mobile health) intervention where cyberhealth educators utilize established social media platforms (e.g., Facebook, texting, and GPS-based mobile applications ["apps"]) designed for social and sexual networking) to improve HIV-related care engagement and health outcomes. As part of the process evaluation of weCare, we conducted 32 interviews with intervention participants ( n = 18) and HIV clinic providers and staff ( n = 14). This article highlights three key intervention characteristics that promoted care engagement, including that weCare is (1) targeted (e.g., using existing social media platforms, similarity between intervention participants and cyberhealth educator, and implementation within a supportive clinical environment), (2) tailored (e.g., bidirectional messaging and trusting relationship between participants and cyberhealth educators to direct interactions), and (3) personalized (e.g., addressing unique care needs through messaging content and flexibility in engagement with intervention). In addition, interviewees' recommendations for improving weCare focused on logistics, content, and the ways in which the intervention could be adapted to reach a larger audience. Quality improvement efforts to ensure that mHealth interventions are relevant for young gay, bisexual, and other men who have sex with men and transgender women are critical to ensure care engagement and support health outcomes.